PEMBERIAN EDUKASI KESEHATAN REPRODUKSI UNTUK MENINGKATKAN PENGETAHUAN REMAJA DI SMA AL-AZHAR BSD CILEUNGSI - Jayanti, Kasyafiya; Petricka, Gracea; Pujiati, Pujiati; Kusmintarti, Arini; Fary, Veronica; Ekawati, Retno; Hayuningsih, Sri; Ambariani, Ambariani (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Adolescent problems related to reproductive health are often caused by a lack of knowledge among adolescents (students) in obtaining accurate information about reproductive health, both from family and school. This is due to the social stigma related to sexual education, preventing teenagers from looking for the right information. Reproductive health issues are still considered taboo and embarrassing to discuss. The activity of providing adolescent reproductive health education is carried out as an effort to provide a correct understanding of reproductive health. Reproductive health for Al-Azhar BSD High School students, Cileungsi District, Bogor Regency, West Java. The method of implementing the activities is carried out face-to-face in the form of lectures and interactive discussions using computer projection media in the form of power points, educational videos, and visual aids (phantoms). Community service activities have been successfully carried out with 197 young men and women participating. Evaluation of results is carried out by assessing the enthusiasm and activeness of participants during outreach activities, both during material explanations and interactive discussion and question and answer sessions. Participants are expected not to be embarrassed when discussing reproductive health in the future so that if there are reproductive health problems they can be examined and treated more optimally. It is necessary to plan a follow-up plan for this community service activity in the form of other education that suits the needs of teenagers.